2017
DOI: 10.4103/sajc.sajc_132_17
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cancer in young in central India: An analysis of rural cancer hospital data

Abstract: Background:Cancers in teenage and young adults (TYAs), though an increasing cause of mortality in our country, have been scarcely studied. The lack of studies of TYAs can significantly affect the outcomes of the youth in the prime of their lives.Aims:The aim of this study was to study the type of cancers in the TYA at a rural cancer center in central India.Design and Methods:A prospective study in the department of medical oncology, from the period of January 2013 till March 2016, was done. Data regarding soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
2
6
1
Order By: Relevance
“…18 Also, a study from Central India revealed hematolymphoid malignancies to be the most common cancer. 29 On comparing with other international studies, our findings were similar to that observed in the workshop summary of the National Cancer Policy Forum of the United States 30 and the Birch classification study from the United Kingdom. 12 Further, while segregating the various cancer subtypes into different age subgroups, embryonal/undifferentiated tumors formed the predominant subtypes in the 1 to 10 and 11 to 20 whereas carcinomas dominated the 21 to 30 and the 31 to 40 age subgroups.…”
Section: Epidemiological Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…18 Also, a study from Central India revealed hematolymphoid malignancies to be the most common cancer. 29 On comparing with other international studies, our findings were similar to that observed in the workshop summary of the National Cancer Policy Forum of the United States 30 and the Birch classification study from the United Kingdom. 12 Further, while segregating the various cancer subtypes into different age subgroups, embryonal/undifferentiated tumors formed the predominant subtypes in the 1 to 10 and 11 to 20 whereas carcinomas dominated the 21 to 30 and the 31 to 40 age subgroups.…”
Section: Epidemiological Characteristicssupporting
confidence: 89%
“…The agerelated trends were no different in Indian studies too, where an incidence of 45 to 55% was seen in the cancers of AYAs in the age group of 30 to 39 years. 29 While assessing the histomorphology, we found carcinoma breast to be the most common among females (29.3%), while NHL was the most common among males (12.6%). Our findings are comparable to other North Indian studies 18,19 as well as with the results from the SEER data.…”
Section: Epidemiological Characteristicsmentioning
confidence: 80%
“…Data collection on a common condition like hypertension has helped us realize its prevalence in a younger age group here [9,10], diabetes mellitus type 2 in India is associated with a low BMI [11]. The common sites of cancers are in the mouth and cervix [12,13], and rheumatoid arthritis is more common than we previously thought [14]. Using this data, we can plan strategies for diagnosis, treatment, and prevention.…”
Section: How Can Commonly Available Data Help In Research?mentioning
confidence: 99%
“…Second, the lack of participation in clinical trials in this age group only complicates things. [8][9][10][11][12][13] The reason for abandonment needs a special mention here as up to 38% of patients abandon their treatment due to…”
mentioning
confidence: 99%